Mass spectrometry imaging: linking molecule profiles to tissue spatial distribution. (February 2013) - Dihazi, Hassan; Bohrer, Rainer; Jahn, Olaf; Lenz, Christof; Majcherczyk, Andrzej; Schmidt, Bernhard; Urlaub, Henning; Valerius, Oliver; Asif, Abdul R
Advances in Bioanalytical Mass Spectrometry: 5th Symposium of the Göttingen Proteomics Forum Mass Spectrometry with Spatial Resolution: MALDI-Imaging and Laser Capture Microscopy Göttingen, Germany, 22 November 2012 MALDI mass spectrometry imaging (MSI) combines the speed and molecular specificity of MALDI-MS detection with information on spatial organization. In the last years, MSI found large application in proteomics research for determining the spatial distribution of compounds in biological tissues and started to draw increasing interest in clinical research. To shed light on the new developments in the field of MSI, the Göttingen Proteomics Forum organized a symposium that was held in Göttingen as part of the series of regular symposia organized by the members of the Göttingen Proteomics Forum. The symposium was on 22 November 2012, with more than 80 delegates that attended the event entitled 'Mass spectrometry with spatial resolution: MALDI-imaging and laser capture microscopy'. The one-day agenda consisted of nine oral presentations from renowned experts in the field with subsequent discussion sessions. As usual, the meeting was fruitful and offered a good platform for discussion between the delegates and proteomics specialists.